Diversity And Abundance of Collembola in Agroforestry Land in UB Forest - Simatupang, Rusdi Ali Sabar; Rahardjo, Bambang Tri (University of Brawijaya, 2023)
Collembola is one of the soil arthropods from the subphylum Hexapoda, namely six-legged arthropods that live in the soil, soil surface, leaf litter, under decomposed stems, and in living fungi. This study aims to determine and examine the diversity and abundance of Collembola on agroforestry land in UB Forest. The preparation and implementation of the research consisted of the determination of plot land, determination of soil sampling points, making holes and soil sampling, extraction of Collembola with a Berlese funnel, sorting and identification of Collembola, soil chemistry analysis and data analysis using the index formula of diversity, evenness, dominance, richness, and abundance and further analyzed with the T-test. The largest population of Collembola is found in pine + coffee land, which is 242 individuals. The highest diversity index is found in pine land, which is 1.04 which is classified as moderate or quite stable. The highest percentage of Collembola species abundance in pine + coffee fields, pine lands, and coffee fields is the family Isotomidae. The lowest percentage of Collembola abundance in pine + coffee fields and pine fields is the family Hypogastruridae, while in coffee fields it is the family Sminthuridae.